2015
DOI: 10.14297/jpaap.v4i2.172
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Learning – Does It Improve Pass Rates and Student Satisfaction?

Abstract: Learning by doing is thought to be one of the most effective ways to learn (Lombardi, 2007). This article explores the findings of a small scale study on one module about whether pass rates and student satisfaction can be improved by introducing authentic learning methods into the classroom by changing the teaching and assessment methods used on a Masters in Business Administration (MBA) module (Accounting and Finance for Decision Making). The pass rates pre and post the changes were monitored and also the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This was attributed to how assessment in higher education in South Africa is based on traditional examination (Bozalek et al, 2013). Simpson (2016) measured the success rate of students after introducing authentic learning methods into the course of Masters in Business Administration students. The result showed that there was improvement in the pass rate of students and the students expressed great satisfaction in the method of learning.…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to how assessment in higher education in South Africa is based on traditional examination (Bozalek et al, 2013). Simpson (2016) measured the success rate of students after introducing authentic learning methods into the course of Masters in Business Administration students. The result showed that there was improvement in the pass rate of students and the students expressed great satisfaction in the method of learning.…”
Section: Introductionmentioning
confidence: 99%
“…Third hypothesis, the results of the calculations continued by using Tuckey test against a group of students who have low self-esteem who studied with authentic methods and groups of students who studied with expository method (A1B2 banding A2B2) is obtained Q calculate = 3,57 is greater than Q table = 2.80 at the level of significance α = 0.05. This means that the ability to interpret religious poems in groups of students with low self-esteem who studied with authentic methods is better than the group of students studied with the expository method (Simpson, 2016). Finally, the fourth hypothesis: the result of calculation of variance analysis of two paths between columns obtained result F calculate = 34.17 is greater than F table = 4.08 at the level of significance α = 0.05 and F table = 7.31 at the level of significance α = 0.01.…”
Section: Resultsmentioning
confidence: 99%
“…According to Jamarah, authentic learning method means a learning method that uses real-world problems and projects and which allows students to explore and discuss these issues in ways that are relevant to them. Authentic learning method is a learning method that allows students to explore, discuss and construct meaningfully concepts and relationships, involving real problems and projects relevant to students (Rule, 2006;Yoon, 2014;Simpson, 2016). The term 'authentic' means original, authentic, and real (Jamarah, 2002).…”
Section: Teaching Methodsmentioning
confidence: 99%
“…The context needs to be all embracing, to provide the purpose and motivation for learning (Herrington & Kervin, 2007). Accordingly, authentic learning requires students to complete tasks that would be carried out in the real-world workplace and it means that theoretical knowledge or concepts are applied to scenarios which are akin to those found in reality (Simpson, 2016) using technologies as cognitive tools. Cognitive tools mean "technologies, tangible or intangible, that enhance the cognitive powers of human beings during thinking, problem solving, and learning" (Jonassen & Reeves, 1996, p. 693).…”
Section: Theoretical Framework For the Design Of An Online Assessmentmentioning
confidence: 99%